Optimization of Vegetative Propagation Techniques for Juniperus communis L. Under Greenhouse Conditions - Marina Sanz Gallego; Miguel Tomás Gascón; Luis Saúl Esteban Pascual (International Journal of Plant Biology)
Juniperus communis L. can be used for essential oils and ornamental purposes, but currently the population is declining in its natural habitats as the seeds are very slow to germinate, with many seeds also empty. These findings could support both the conservation of J. communis and its adoption in sustainable agricultural systems. This study investigated the potential of vegetative propagation evaluating the effects of rooting medium, gender, and Indole 3-Butyric Acid (IBA) treatment on the rooting success of J. communis cuttings. Two types of rooting medium (RM_I vs. RM_II), gender (male vs. female) and two IBA concentrations (0 vs. 4000 ppm) were used. Rooting medium I (RM_I) consists of substrate and perlite (50% + 50%), and rooting medium II (RM II) contains unfertilized blonde peat (65%), substrate (25%), and perlite (10%). The results show the influence of rooting medium, IBA treatment, and gender on the rooting percentage and the number of the primary roots. Female cuttings are more likely to induce rooting than male cuttings (29.69% vs. 19.90%), and the RM_II produces a higher percentage of rooting than RM_I (28.89% vs. 20.70%). In relation to the number of roots per cutting, RM_II was higher than RM_I (7.46 vs. 6.04). Interaction between rooting medium and IBA treatment showed significant differences (p ≤ 0.05) in the rooting percentage. Results showed that cuttings treated with 4000 ppm IBA in RM_II achieved the highest rooting percentage (45.57%), with female cuttings outperforming male cuttings.